Positive academic leadership how to stop putting out fires and begin making a difference - Buller, Jeffrey L. (John Wiley & Sons, 2013)
This book gives academic leaders new insights and practical tools, as well as language and strategies, for fostering a more constructive leadership style that plays to the strengths rather than the weaknesses of their institutions.